2013
DOI: 10.1111/1753-0407.12067
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and decompensated cirrhosis: Risk of hepatic encephalopathy in different age groups (糖尿病与失代偿性肝硬化:不同年龄组的肝性脑病风险)

Abstract: Both DM and older age are independently associated with HE in patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 22 publications
0
27
0
1
Order By: Relevance
“…Some cirrhosis patients are known to be at greater risk of HE than others, particularly those with previous episodes, but also those with hyponatremia, poor metabolic liver function [1], or a transjugular intrahepatic portosystemic shunt (TIPS). Diabetes mellitus, too, has been associated with a higher prevalence of HE [2][3][4][5], although this has not been a consistent finding [6]. Moreover, all previous studies addressing this question used a cross-sectional study design, meaning that they could not determine whether diabetes increased the incidence or the duration of HE episodes.…”
Section: Introductionmentioning
confidence: 99%
“…Some cirrhosis patients are known to be at greater risk of HE than others, particularly those with previous episodes, but also those with hyponatremia, poor metabolic liver function [1], or a transjugular intrahepatic portosystemic shunt (TIPS). Diabetes mellitus, too, has been associated with a higher prevalence of HE [2][3][4][5], although this has not been a consistent finding [6]. Moreover, all previous studies addressing this question used a cross-sectional study design, meaning that they could not determine whether diabetes increased the incidence or the duration of HE episodes.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al reported that the presence DM increased the risk for decompensation events (including HCC) compared to patients with cirrhosis only, [28] a finding supported by other earlier studies. [2931] In addition, although successful HCV eradication with antiviral therapy reduced HCC risk, [32,33] hyperglycemia, and other unfavorable predictors of antiviral treatment efficacy [34,35] may indirectly promote HCC development. Finally, metabolic syndrome, of which DM is a component, increases the risk of nonalcoholic steatohepatitis (NASH), which can lead to HCC.…”
Section: Discussionmentioning
confidence: 99%
“…For cirrhotic patients, the coexistence of DM with cirrhosis might increase the risk of adverse progression and cause severe complications. According to prior studies, increases in orocecal transit time and intestinal bacterial growth due to diabetes may increase blood ammonia levels, which could lead to a high prevalence of HE among cirrhotic patients with diabetes [18] [19]. However, in this study, although univariate analysis indicated that diabetes was significantly associated with the incidence of HE, the association between DM and the presence of HE did not reach statistical significance in multiple logistic regression analysis after adjusting for several other factors, such as age, BMI, WBC, INR, SBP, total bilirubin, ALT, AST, albumin, and PA. SBP is another important complication among cirrhotic patients that requires hospitalization and treatment with antimicrobial agents; this condition can lead to poor quality of life and shortened survival times [18] [20] [21].…”
Section: Discussionmentioning
confidence: 99%